2016
DOI: 10.1371/journal.pone.0169191
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Evolutionary History of an Extinct South American Freshwater Snail Based on Historical DNA

Abstract: Highly oxygenated freshwater habitats in the High Paraná River (Argentina–Paraguay) were home to highly endemic snails of the genus Aylacostoma, which face extinction owing to the impoundment of the Yacyretá Reservoir in the 1990s. Two species, A. chloroticum and A. brunneum, are currently included in an ongoing ex situ conservation programme, whereas A. guaraniticum and A. stigmaticum are presumed extinct. Consequently, the validity and affinities of the latter two have remained enigmatic. Here, we provide th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…The secondary structure of the 12S rRNA of P. reevei ( Figure 6 ) and P. aulanieri ( Figure S3 ) had an identical organization of four structural domains, with Domain III as the most conserved region, allowing its successful PCR across a wide variety of taxa [ 48 ]. Here, we found that the structure of Domain III in P. reevei and P. aulanieri is similar to previous reports in other mollusks [ 27 , 49 , 50 , 51 ]. On the other hand, Domains I and II have been poorly studied and they were difficult to infer in both species.…”
Section: Resultssupporting
confidence: 91%
“…The secondary structure of the 12S rRNA of P. reevei ( Figure 6 ) and P. aulanieri ( Figure S3 ) had an identical organization of four structural domains, with Domain III as the most conserved region, allowing its successful PCR across a wide variety of taxa [ 48 ]. Here, we found that the structure of Domain III in P. reevei and P. aulanieri is similar to previous reports in other mollusks [ 27 , 49 , 50 , 51 ]. On the other hand, Domains I and II have been poorly studied and they were difficult to infer in both species.…”
Section: Resultssupporting
confidence: 91%
“…In some cases, the identity and relationships of extinct taxa have been addressed and clarified through study of ancient DNA from dried tissue (e.g. Villanea et al 2016; Vogler et al 2016). Unfortunately, this approach is not applicable for Mabille’s syntypes because they consist only of shells devoid of any dried tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The radula and jaw were cleaned following a modification of the non-destructive method described by Holznagel (1998) and Vogler et al (2016) : the structures were separated from the mass of tissue and placed in 1.5-ml microtubes containing 500 µl NET buffer (1 ml 1M Tris pH 8.0, 2 ml 0.5 M ethylenediaminetetraacetic acid, 1 ml 5 M NaCl, 20 ml 10% (w/v) sodium dodecyl sulfate, 76 ml water) and 10 µl of Proteinase K (20 mg/ml) were added. The samples were then incubated at 37 °C with a subsequent renewal of the NET buffer and Proteinase K to verify the absence of tissue.…”
Section: Methodsmentioning
confidence: 99%